Ву юись вуюись: кылбуръёс / Герман Ходырев - Ходырев Герман Алексеевич (Удмуртия, 2013)
Экземпляры: (20150320) / Инвентарный номер: 2020 / Цена: 115.00 / Сис.шифр: С(Удм) / Авт.знак: Х 69 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)